2018
DOI: 10.3390/cells7090138
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Altered miRNA Expression and DNA Methylation of the DLK1-DIO3 Region in Azacitidine-Treated Patients with Myelodysplastic Syndromes and Acute Myeloid Leukemia with Myelodysplasia-Related Changes

Abstract: The DLK1–DIO3 region contains a large miRNA cluster, the overexpression of which has previously been associated with myelodysplastic syndromes (MDS). To reveal whether this overexpression is epigenetically regulated, we performed an integrative analysis of miRNA/mRNA expression and DNA methylation of the regulatory sequences in the region (promoter of the MEG3 gene) in CD34+ bone marrow cells from the patients with higher-risk MDS and acute myeloid leukemia with myelodysplasia-related changes (AML-MRC), before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…In our recent study, we demonstrated increased expression of 14q32 miRNAs in CD34+ cells in advanced stages of MDS and in AML-MRC and associated this elevation with poor outcome. Moreover, the increased intracellular levels of 14q32 miRNAs were reduced after AZA treatment [73]. Based on the present data, it seems that the levels of 14q32 miRNAs have opposite trends in HSCs and in plasma in different stages of the disease, i.e., these miRNAs are released into the extracellular environment in early, pro-apoptotic stages of MDS but are retained intrinsically along with disease progression.…”
Section: Discussionmentioning
confidence: 54%
“…In our recent study, we demonstrated increased expression of 14q32 miRNAs in CD34+ cells in advanced stages of MDS and in AML-MRC and associated this elevation with poor outcome. Moreover, the increased intracellular levels of 14q32 miRNAs were reduced after AZA treatment [73]. Based on the present data, it seems that the levels of 14q32 miRNAs have opposite trends in HSCs and in plasma in different stages of the disease, i.e., these miRNAs are released into the extracellular environment in early, pro-apoptotic stages of MDS but are retained intrinsically along with disease progression.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, there is a need for new biomarkers to better improve patient prognosis [12, 13]. Several other studies had identified DNA methylation gene as prognostic biomarkers of nasopharyngeal carcinoma and acute myeloid leukemia [14, 15]. In the current field of TETs, tumor size, gene mutation, protein expression, and miRNA had been reported to affect the prognosis of patients with TETs and potentially be used as prognostic biomarkers for TETs [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies had identified DNA methylation gene as prognostic biomarkers of nasopharyngeal carcinoma and acute myeloid leukemia [14, 15]. In the current field of TETs, tumor size, gene mutation, protein expression, and miRNA had been reported to affect the prognosis of patients with TETs and potentially be used as prognostic biomarkers for TETs [15, 16]. However, targeting DNA methylation sites as prognostic biomarkers for TETs have not been explored, and our current study is the first to report DNA methylation sites as biomarkers for the prognosis of patients with TETs.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the impact of the identified gene markers on prognosis and HMA response, we applied the gene set-level scores (i.e., the mean expression of leading edge genes of 20 GO terms in Table 2) in independent data sets. We obtained publicly available gene expression profiles of 123 MDS patients with overall survival (GSE58831) 37 and 32 patients with AZA treatment history (13 responders and 19 non-responders; GSE77750) 38,39 . For survival (GSE58831), MDS patients whose gene expression profiles resembled those of AZA responders in our study ('responder-like') showed better survival (green in Fig.…”
Section: Validation Of Azacitidine Sensitivity Signatures In Independmentioning
confidence: 99%